On the Moral Equivalence of Global Commodities: Placing the Production and Consumption of Organic Bananas - Trauger , Amy; Murphy , Andrew (The International Journal of Sociology of Agriculture and Food, 2013)
Rapid change and growth in certified organic food sectors has led to the development of export-orientated certified organic food production in developing economies. This lengthening of the supply chain requires the development and implementation of meaningful standards to make the production process in developing countries legible to consumers in developed economies. As an example of the globalization of organic foods and analysis of its corresponding standards, this article discusses the political, cultural and economic context for the supply of and demand for organic bananas in the Dominican Republic and the United Kingdom, respectively. We focus on the role of certification schemes that have emerged in response to this global expansion, and suggest that, contrary to consumer expectations, there are political, economic and environmental outcomes that are inconsistent with organic standards.